2016
DOI: 10.1055/s-0036-1579739
|View full text |Cite
|
Sign up to set email alerts
|

Immunology of Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is considered a prototypic autoimmune disease of the central nervous system (CNS). A complex genetic background with the HLA-DR15 haplotype as the main genetic risk factor and over 100 mostly immune-related minor risk alleles as well as several environmental factors contribute to the etiology of MS. With respect to pathomechanisms, autoimmune inflammation in early MS is primarily mediated by adaptive immune responses and involves autoreactive T cells, B cells, and antibodies, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
171
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(192 citation statements)
references
References 171 publications
1
171
1
5
Order By: Relevance
“…The incidence of MS is around two to three times greater among women than men. Correlation studies on racial differences in the MS prevalence rates worldwide have revealed that the Caucasians appears to have a higher risk than other populations 22 . The majority of the subjects in the present study showed the RRMS clinical form as in previous reports, which have shown approximately 80% of the patients will initially present this form 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of MS is around two to three times greater among women than men. Correlation studies on racial differences in the MS prevalence rates worldwide have revealed that the Caucasians appears to have a higher risk than other populations 22 . The majority of the subjects in the present study showed the RRMS clinical form as in previous reports, which have shown approximately 80% of the patients will initially present this form 11 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear what exactly causes the disease. One of the initiators of MS is antigen from virus or bacteria that is similar to the myelin basic protein peptide [10,11] . The autoimmunity hypothesis is now being challenged since the fi nding that, like many other neurodegenerative disorders, gray matter lesions and brain atrophy are detectable before MS onset [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…MS hastalığında CD4+ T helper (Th) 1 ve Th17 hücreleri miyelin kılıf bileşenlerini yabancı antijen olarak algılarlar ve miyeline karşı otoreaksiyon geliştirirler (1,6).…”
Section: Klinik Bulgularunclassified